Prediction of oxygen content of nappe, transition, and skimming flow regimes in stepped-channel chutes - Baylar, Ahmet; Bagatur, Tamer; Emiroglu, M. Emin (Ice Publishing, 2007)
In a stepped-channel chute, the chute face is provided with a series of steps, from near the crest to the toe. Like many other high-speed flow configurations in hydraulic engineering, stepped-channel chute flows are characterized by the large amount of self-entrained air. Air entrainment on stepped-channel chutes is also recognized for its contribution to the oxygen transfer. The flow conditions in stepped-channel chutes have been classified into nappe flows, transition flows, and skimming flows. In this study, the aeration efficiency of stepped-channel chutes was investigated, and in particular, the effect of varying flow regimes. The results indicated that the nappe flow regime led to the larger aeration efficiency than the other flow regimes. Moreover, the mass transfer equations were developed to predict the aeration efficiency of the stepped-channel chutes in terms of dissolved oxygen. There is good agreement between the measured aeration efficiency values and the values computed from the predictive equations.
Keywords: aeration efficiency; oxygen transfer; stepped-channel chute; skimming flow; transition flow; nappe flow